Enhancing Productivity and Profitability of Tribal Farmers of Jharkhand through Institutional Linkages - Singh, B. K.; Sharma, Ambrish Kumar; Sharma, Nishi; Ratan, R. P. Singh; Lakra, Valaria; Singh, Kishan (Indian Journal of Extension Education, 2016)
Public sector extension continues to be the most important source of information for majority of farmers but its  performance is under scrutiny for quite some time and questions are being raised on its capability to deliver goods and  services in the rapidly changing environment. The shifting emphasis of Indian agriculture towards diversification,  commercialization, sustainability and efficiency has made it necessary to look for new approaches and models for  extension. The Indian Agricultural Research Institute (IARI) over the period has experimented with different extension  approaches and models which have immensely contributed to the development of roadmaps for national extension  systems. One such model of Institutional partnership based extension to diffuse IARI technologies all over India, a  partnership led extension was initiated under National Extension Programme. Under this programme the IARI varieties  and production technologies were diffused in collaboration with 15 ICAR Institutes and SAUs for quick and wider spread  to a large number of farmers in different parts of the country. One such collaboration with Birsa Agricultural University  (BAU), Ranchi was initiated to address the production problem of tribal farmers of Jharkhand during year 2007-08 (Rabi  Season). The specific objectives of the project are to demonstrate improved seeds of major crops and to produce quality  seed by the farmers themselves. Although, agriculture is main source of livelihood for 80 per cent of the population in  Jharkhand, it is characterized by reliance on low investment, low productivity and mono cropping with paddy as the  overriding crop. Under this collaboration suitable crop varieties of paddy, wheat, mustard, lentil and vegetables were  demonstrated on farmers' fields. Farmers were continuously giving their opinion towards selected traits of the  demonstrated improved varieties of rice. Paddy variety Pusa 2511 was preferred by the farmers due to its high yield,  aroma and long grain quality. It has been accepted and adopted by the farmers in the demonstration villages as well as  nearby villages. Rice variety Jaldi Dhan-13 was demonstrated during kharif 2012 and 2013 was liked owing to its coarse  grains for their own consumption as they perform hard physical activities and found this variety suitable for their upland  areas. Among rabi crops, wheat variety HD-2733 was liked by farmers due to its high yield, varieties HD-2985 and HD 2932 due to their relatively early maturing trait. Pusa Jaikisan variety of mustard was preferred by the farmers due to its  high yield and relatively more oil content. Majority of the farmers preferred to grow mustard with wheat, due to the fact  that area under irrigation was relatively less. The farmers also revealed that varieties provided by IARI were insect-pest  and disease resistant. The paper describes the process and outcome of the IARI interventions for having its implications  among extension professionals and practitioners in India.
Keywords: Productivity; profitability; tribal farmers